Determination of 3‐D Alumina Grain Orientation, Size, Shape, and Growth Kinetics from 2‐D Data in Nextel™ 610 Fibers. Issue 7 (8th April 2015) - Hay, Randall S.; Fair, Geoff E.; Keller, Kristin A.; Tidball, Travis; Suvaci, E.
<x xml:space="preserve">Abstract</x> Nextel™ 610 alumina fibers were heat‐treated at 1100°C–1500°C for 1–100 h in air. Grain size distributions (GSDs) and grain orientation distributions (ODs) with respect to the fiber axis were characterized by analysis of TEM images from longitudinal fiber sections. The 2‐D GSDs and ODs were characterized as ellipses. 3‐D GSDs and ODs were calculated by fitting distributions of oriented oblate ellipsoids to 2‐D GSDs and ODs formed by ellipsoid–section‐plane intersections. The standard deviations (SDs) of log‐normal GSDs consistently increased with grain size, which is not diagnostic of normal grain growth. The grain aspect ratio (α) and the tendency of the short grain axis to orient perpendicular to the fiber axis also increased with grain size, resulting in more textured fibers at larger grain sizes. Average 3‐D grain sizes were larger than 2‐D sizes for GSDs with small SDs, but smaller for GSDs with large SDs because of under sampling of small grains. 3‐D grain growth kinetics had the same 815 kJ/mol activation energy as that found by 2‐D analysis, but the grain growth exponent m of 6.0 was larger and the pre‐exponential factor much smaller. Expressions for 3‐D log‐normal GSDs as a function of heat treatment temperature and time were determined. α‐distributions and ODs were determined as a function of grain size. Methods for determining 3‐D GSDs are discussed.